Peri-operative peripheral nerve injury (Health Renaissance, 2014)
Peripheral nerve injury in peri-operative period is the topic of interest especially for the anesthesiologists because the concentration of rest of the operation theatre team lies on the positioning of the patient required for the surgical exposure rather than towards the stretching or compression of the nerves. Etiology of peri-operative peripheral nerve injury (PPNI) is complex and multifactorial. Prevention of injury and its consequences to some extent can be done with the alertness of the concerned surgical team and the anesthesiologist. DOI: http://dx.doi.org/10.3126/hren.v11i3.9643 Health Renaissance 2013;11(3):260-266